Peningkatan Kesadaran Masyarakat Dalam Menunaikan Zakat, Infaq, Sedekah Dan Wakaf (ZISWAF) (UIN Sunan Kudus, 2018)
Increasing public awareness in performing ZISWAF is very urgent. This can be done by internally increasing community religiosity through the preaching of ulama who are still about ZISWAF. And the external side, by increasing accountability and transparency in managing ZISWAF, and increasing government participation in socializing regulations on ZISWAF, as well as giving accreditation to Zakat, Infaq, charity and endowments management and sanctions for institutions that commit violations